Perancangan Resor Di Kampar Kiri Hulu Dengan Pendekatan Arsitektur Posmodern - Julius Eduvin Panjaitan; Pedia Aldy; Yohannes Firzal (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Tanjung Belit village in Kampar Kiri Hulu subdistrict has been transformed to be tourism object and it is passed through by a river (Sebayang River). This place does not provide adequatefacility for accommodation. That is the reason why there has to be a temporary accommodation, such as resort. Buildings with the characteristics of rumah lontiok still stand in this region.However, the villagers had not used those characteristics. The villagers focus more on maximizing the function of the shapes and space of their house. To reflect characteristics of the place where the resort is built, Postmodern Architecture is the suitable theme for this resort design. By using Postmodern Architecture topic as design approach, hence we get the Compound of Composure andGregarious concept. Composure is interpreted as modern architeture which emphasizes on function and simple form, and Gregarious is interpreted as Lontiok Architecture which has more shapes and carved objects. The compatibility of the concept is applied on site pattern and building form including zoning, mass order, outdoor planning, mass formation, indoor planning, and interior.Keyword:Resort, Compound, Postmodern Architecture